Decision-making process for esthetic treatment of gummy smile: A surgical perspective - Avishek Das (Wolters Kluwer Medknow Publications, 2021)
Gummy smile is a quite frequently found esthetic alteration characterized by excessive display of gingiva during smiling. Several causes have been implicated in the literature, but a dearth of clinical decision-making process has been found in the surgical treatment of excessive gingival display. An external bevel gingivectomy with osseous correction was performed in anterior maxillary region in accordance with the proposed decision-making process. The clinical observation at 1 month postoperatively revealed restoration of natural smile with 1–2 mm of facial gingival display. The outcome seems to suggest that this proposed decision-making process can provide valid treatment options for gummy smile cases.